2018
DOI: 10.1186/s12879-018-3453-6
|View full text |Cite
|
Sign up to set email alerts
|

No polymorphisms in K13-propeller gene associated with artemisinin resistance in Plasmodium falciparum isolated from Brazzaville, Republic of Congo

Abstract: BackgroundIn the Republic of Congo, artemisinin-based combinations have been recommended for the treatment of uncomplicated malaria since 2006. However, the emergence of resistant parasites again these combinations in Southeast Asia is a threat for the control of this disease, especially in sub-Saharan Africa where the weight of the disease is important. Indeed, polymorphisms in Plasmodium falciparum K13-propeller gene have been involved in variations of drug sensitivity of Plasmodium falciparum to artemisinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 20 publications
9
13
0
Order By: Relevance
“…Our study on samples collected in Bangui between 2017 and 2019 demonstrate the presence of one non-synonymous mutation (Y653N) and three synonymous mutations (frequency of 2.1%). This frequency of PfKelch13 mutants is similar to those observed in neighboring countries (Brazzaville Congo, certain regions of Cameroon), which showed frequencies of 1.57% and 2.9%, respectively [26,27], confirming the absence of artemisinin resistance in Central Africa [20]. The only previous data on PfKelch13 polymorphism performed in 2014 in the CAR (K13 artemisinin resistance multicenter resistance, KARMA study), revealed a 4.5%…”
Section: Frequency Of Mutations In Thesupporting
confidence: 80%
“…Our study on samples collected in Bangui between 2017 and 2019 demonstrate the presence of one non-synonymous mutation (Y653N) and three synonymous mutations (frequency of 2.1%). This frequency of PfKelch13 mutants is similar to those observed in neighboring countries (Brazzaville Congo, certain regions of Cameroon), which showed frequencies of 1.57% and 2.9%, respectively [26,27], confirming the absence of artemisinin resistance in Central Africa [20]. The only previous data on PfKelch13 polymorphism performed in 2014 in the CAR (K13 artemisinin resistance multicenter resistance, KARMA study), revealed a 4.5%…”
Section: Frequency Of Mutations In Thesupporting
confidence: 80%
“…This finding is similar to those from studies in Africa [9,29,[40][41][42][43][44] reporting a lack of the pfk13 mutations associated with artemisinin combination therapeutic resistance that have been identified in Southeast Asia [40,[45][46][47][48].…”
Section: Discussionsupporting
confidence: 89%
“…Absence of pfk13 mutations associated with artemisinin resistance is further evidence that parasites remain susceptible to artemisinin derivatives in Guinea. This nding is similar to those studies in Africa [11,30,[39][40][41][42] reporting a lack of the pfk13 mutations associated with artemisinin combination therapeutic resistance that have been identi ed in Southeast Asia [40,[43][44][45].…”
Section: Discussionsupporting
confidence: 89%